2011
DOI: 10.1038/modpathol.2011.5
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 expression by primary tumor cells correlates with melanoma progression from radial to vertical growth phase and development of metastatic competence

Abstract: Down-regulation of the immune system facilitates tumor progression at different stages of cutaneous melanoma. Sentinel nodes, the first lymph nodes on lymphatics draining directly from a primary melanoma are immune down-regulated by tumor-generated immune-suppressive cytokines including interleukin-10. To better understand the kinetics of sentinel node suppression, we investigated interleukin-10 expression by melanoma cells and tumor-associated macrophages and lymphocytes at different stages of primary melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 44 publications
5
99
0
6
Order By: Relevance
“…Mean survival of the CD163 high and low cohorts was 39 AE 10 and 286 AE 95 weeks, respectively (P ¼ 0.01 by the log-rank test). IL-10 has well-established immunomodulatory properties and is elaborated by a number of different cell types in a variety of cancers including melanoma (42), non-small cell lung cancer (43), and B-cell lymphoma (44) as well as glioblastoma multiformes. This has led to speculation that IL-10 contributes to an immunosuppressive tumor microenvironment, a concept that is challenged by the observation ÃÃÃ , statistically significant difference between the groups determined by the MannWhitney U test (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Mean survival of the CD163 high and low cohorts was 39 AE 10 and 286 AE 95 weeks, respectively (P ¼ 0.01 by the log-rank test). IL-10 has well-established immunomodulatory properties and is elaborated by a number of different cell types in a variety of cancers including melanoma (42), non-small cell lung cancer (43), and B-cell lymphoma (44) as well as glioblastoma multiformes. This has led to speculation that IL-10 contributes to an immunosuppressive tumor microenvironment, a concept that is challenged by the observation ÃÃÃ , statistically significant difference between the groups determined by the MannWhitney U test (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that lung cancer cells are able to produce immunosuppressive factors in the tumor microenvironment. For example, they can secrete a soluble form of MHC class I chain-related molecule A, inducing downregulation of NKG2D expression of CD8 IL-10 or TGF-b or the tryptophan catabolic enzyme indoleamine 2,3-dioxygenase, which are key players involved in the inhibition of immune responses and enhancing the proliferation of cancer cells (56,57). Lung cancer cells, among other components of the tumor microenvironment, express chemokine receptors and produce chemokines that regulate the trafficking of immune and cancer cells.…”
Section: Tumor Intrinsic Factors With Immunosuppressive or Immunogenimentioning
confidence: 99%
“…BCC is regarded as an indolent (slow growing) cancer with limited metastatic potential. While IL-10 expression by melanoma cells correlates with melanoma progression and development of metastatic competence (18), there is no clear correlation between IL-10 expression and tumor invasiveness of BCC. IL-10 can be detected by both aggressive BCC and nonaggressive BCC such as superficial BCC.…”
Section: Il-10mentioning
confidence: 96%